(untitled) (Global Journal of Management and Business Research, 2022)
In the light of recent disruptive events global supply chains have displayed their vulnerability which has stressed the importance of procurement in modern practice This study aims to analyse if the procurement function can be reconsidered as a primary activity in Porter s 1985 value chain